Issues on the initial impact of CEFR in Thailand and the region - Foley, Joseph (Universitas Pendidikan Indonesia, 2019)
This paper outlines the revised version of the Common European Framework of Reference Languages: Learning, Teaching and Assessment (CEFR, 2018), followed by the Frameworks of Reference for English Language Education in Thailand (FRELE-TH). The approaches taken in Japan, Vietnam, Malaysia, and China based on CEFR will also be briefly discussed. A number of issues identified by various researchers have affected the implementation of CEFR, such as the lack of background knowledge of the goals of CEFR, the initial stress on language assessment for teachers and learner/users, the apparent lack of follow-up in terms of training, materials and expertise. Finally, the implementation of CEFR in the region will be emphasized in reference to Teaching English as an International Language (TEIL) and reflected on how this approach could be implemented in the local contexts of Asia.